A Cannibalistic Feast. The Universal Pain of Fauna and Flora in Tadeusz Miciński’s Niedokonany - Borek, Bartłomiej (The Motifs of Fauna and Flora in Literature and Culture, 2018)
Since antiquity the depiction of nature has been involving subjective observation of the space surrounding, and often has been overwhelming, its observers. Beginning with the motif of locus amoenus and concluding with locus horridus, literary representations of fauna and flora have become more and more intriguing. The portrayal of nature in Tadeusz Miciński’s poem Niedokonany seems to be an adequate example of such a riveting depiction. This peculiar sea of darkness, much like an enclave without an exit, is a trap for anyone who dives into it.In the article the author presents significant findings about the gnostic view of nature. Special attention is paid to the motifs of cricket, phoenix, lotus in Egyptian culture, and to the motif of predatory wasp, analysed in the context of the Bergsonian interpretation of the insect’s maternity phenomenon.